2009
DOI: 10.4103/0019-5413.49387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hydroxyapatite and beta-tricalcium phosphate mixed with bone marrow aspirate as a bone graft substitute for posterolateral spinal fusion

Abstract: Background:Autologous cancellous bone is the most effective biological graft material. However, harvest of autologous bone is associated with significant morbidity. Since porous hydroxyapatite and beta-tricalcium phosphate are biodegradable materials and can be replaced by bone tissue, but it lacks osteogenic property. We conducted a study to assess their use as a scaffold and combine them with bone marrow aspirate for bone regeneration using its osteogenic property for posterolateral spinal fusion on one side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 12 publications
(19 reference statements)
2
26
0
Order By: Relevance
“…This collagen-free layer has an active role absorbing extracellular proteins such as growth factors [19]. Thus, bone grafts containing more HA show more radiopacity during the time of healing [18]. The effect of Osteon  (70% of HA) graft observed in our study seems to be related to this process.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This collagen-free layer has an active role absorbing extracellular proteins such as growth factors [19]. Thus, bone grafts containing more HA show more radiopacity during the time of healing [18]. The effect of Osteon  (70% of HA) graft observed in our study seems to be related to this process.…”
Section: Discussionsupporting
confidence: 49%
“…However, if the graft resorption takes place before the new bone is formed, the bone healing rate may be affected [16]. When this ceramic is mixed with HA, which is a low resorption rate graft [2,17], it improves the formation and remodeling of new bone by providing adequate mechanical resistance [18].…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, Bansal et al reported that HA in combination with β-tricalcium phosphate and bone marrow aspirate was a safe option for spinal fusion and had comparable effectiveness to an autologous bone graft; the major advantage of this option is the avoidance of donor site morbidity. 2 Based on the results obtained from the current study, it is recommended that future research on HA granules or HA granules plus PRP focuses on the use of these materials in combination with spinal fusion instrumentation in larger-sized animal models. In spinal surgery, higher fusion rates are achieved when instrumentation is used.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies in the literature are in agreement with these findings. 2,21,22 The porous characteristics of HA potentially affect the histological outcomes of posterolateral lumbar fusion; Motomiya et al found that the highly interconnected porous structure of HA was a promising environment for spinal fusion in a rabbit model in terms of producing fusion masses with higher cellular viability. 23 In addition, Bansal et al reported that HA in combination with β-tricalcium phosphate and bone marrow aspirate was a safe option for spinal fusion and had comparable effectiveness to an autologous bone graft; the major advantage of this option is the avoidance of donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation